2019
DOI: 10.1177/0163443719857616
|View full text |Cite
|
Sign up to set email alerts
|

Public service media beyond the digital hype: distribution strategies in a platform era

Abstract: The notion of public service media is used to describe public broadcasters’ provision of services that contribute to the democratic, cultural and social objectives of society, and this on multiple devices and across various technologies. While most research focuses on the theoretical case for public service media, this contribution analyses how public broadcasters strategically position themselves as providers of public service media. What are their distribution strategies in a market that is no longer dominat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 26 publications
1
31
0
9
Order By: Relevance
“…Regardless of the size, market power or model adopted by a public service broadcaster in each specific context, these organizations experienced a quite challenging transformation since the mid-1990s, as online and digital media started to develop, changing the communication markets for good. Public service broadcasters then evolved into Public Service Media (PSM) organizations (Bardoel and Lowe 2007 ; Brevini 2010 ), a process that authors like Donders ( 2019 , p. 1012) consider still a “work in progress.” Their traditional activity in the radio and television market was expanded and PSM organizations launched catch-up and on-demand platforms (Rodríguez-Fernández et al 2018 ), developed new ways to connect with their audiences through social media (van Dijck and Poell 2015 ), experimented with innovative narratives, including immersive (Gutiérrez-Caneda et al 2020 ) and transmedia products (Franquet and Villa Montoya 2014 ) and exploited the personalization potentialities posed by the new digital environment (Schwarz 2016 ; Vaz Álvarez et al 2020 ). This digital expansion was also accompanied by major organizational reforms, affecting the organizations’ charts and newsrooms (Larrondo et al 2016 ), which had to be redesigned in order to adapt to new workflows of content production ; its culture, which must evolve from protectionism to a partnership framework (Głowacki and Jackson 2019 ); and its funding models, which in some cases (such as the license fee attached to the ownership of a television set) became unsustainable in the face of new consumption habits (Warner 2019 ).…”
Section: Public Service Media In the Digital Age: Keeping Up With Conmentioning
confidence: 99%
“…Regardless of the size, market power or model adopted by a public service broadcaster in each specific context, these organizations experienced a quite challenging transformation since the mid-1990s, as online and digital media started to develop, changing the communication markets for good. Public service broadcasters then evolved into Public Service Media (PSM) organizations (Bardoel and Lowe 2007 ; Brevini 2010 ), a process that authors like Donders ( 2019 , p. 1012) consider still a “work in progress.” Their traditional activity in the radio and television market was expanded and PSM organizations launched catch-up and on-demand platforms (Rodríguez-Fernández et al 2018 ), developed new ways to connect with their audiences through social media (van Dijck and Poell 2015 ), experimented with innovative narratives, including immersive (Gutiérrez-Caneda et al 2020 ) and transmedia products (Franquet and Villa Montoya 2014 ) and exploited the personalization potentialities posed by the new digital environment (Schwarz 2016 ; Vaz Álvarez et al 2020 ). This digital expansion was also accompanied by major organizational reforms, affecting the organizations’ charts and newsrooms (Larrondo et al 2016 ), which had to be redesigned in order to adapt to new workflows of content production ; its culture, which must evolve from protectionism to a partnership framework (Głowacki and Jackson 2019 ); and its funding models, which in some cases (such as the license fee attached to the ownership of a television set) became unsustainable in the face of new consumption habits (Warner 2019 ).…”
Section: Public Service Media In the Digital Age: Keeping Up With Conmentioning
confidence: 99%
“…Researching how public service broadcasters approach online distribution in a more competitive and internationalized market of VoD content, Donders (2019Donders ( , p. 1012 finds that "[t]he online strategies of some public broadcasters are directionless, although others, admittedly, have developed more mature schemes." She characterizes PSB organizations' transition to PSM in five phases (Ibid., p. 1013): 1) the experimental phase, where "public broadcasters realize that the Internet offers possibilities to distribute content in a different manner"; 2) the panic phase, "when public broadcasters realise that other companies or even some private individuals are more successful than they are at attracting audience attention online.…”
Section: Datafication and Public Service Mediamentioning
confidence: 99%
“…For public service broadcasters, the decisions and investments needed to launch VoD services and other digital services were thus not necessarily slowed down by a fear of losing advertising revenue or changing business models, as in the case of commercial to private broadcasters (Murschetz & Prandner, 2018), but were, as Donders (2019) shows, dependent on both internal organizational dynamics and the media political situation in the respective countries with regard to the PSB online/PSM remit. As an example, DR has been allowed teleservice-based services since 2000 (Kulturministeriet, 2000, §7 stk.…”
Section: Datafication and Public Service Mediamentioning
confidence: 99%
“…Studies have found that, in a rapidly evolving digital media environment, innovation is important for PSM, but their attitude towards innovation in products, processes or management are rather problematic -"the results show evidence of paradoxical tensions surrounding the maintenance of the status quo versus disruption" (Evans 2018: 18). "The fact that the fairly simple distribution strategy of the radio and broadcasting era has been gradually superseded by more complex and often unsynchronised (in terms of the balance of relative power) distribution strategies clearly requires some form of organisational change" (Donders 2019(Donders : 1023.…”
Section: Resourcesmentioning
confidence: 99%